Passive component’s real behavior models and simulation for the frequency domain - Herrera-Vega, Luis Arturo (2014)
The development of new electrical devices in our times involves, at first, a fundamental stage of simulation modeling and theoretical behavior at the frequency domain before proceeding with the experimental steps necessary to consolidate these ideas into a new product good enough to be used in our society. In this matter, understanding the actual operation of passive components is essential to describe key characteristics that define the actual performance of the evolving system. Fundamentally, there are three most commonly used electrical elements, namely: resistance, capacitors and inductors, essential to generate new sensors that base their operation on the electromagnetic induction phenomenon. In good theory, these elements can be modeled with simple mathematical equations by means of circuit analysis techniques in the sinusoidal permanent state, but in practice, it is clear these devices exhibit a very different behavior, due inter alia, to material’s nonlinearities used for manufacturing. This document aims to summaryze a series of simple conceptual models developed by several authors that approaches, somewhat, a more precise performance characterization of these devices by varying the operating frequency, as well as a brief description of the different materials used on its construction, with the aim of expanding the theoretical overview for a better understanding and further characterization of common electrical systems.